Giant peritoneal loose body: a challenging diagnosis in an asymptomatic patient - Silva, André A.; Reis, Rui A.; Rocha, Catarina C.; Pinto-de-Sousa, João (International Surgery Journal, 2023)
Peritoneal loose bodies are rare surgical or imaging findings. In most cases, PLBs are small in size, usually from 5 to 20 mm. Giant PLBs measuring more than 50 mm are even rarer. Only a few cases of giant PLBs have been reported. The authors report a case of a giant PLB with only mild symptoms and with no preoperative diagnosis, highlighting the importance of being aware of the characteristic findings of these lesions to establish a correct diagnosis, avoiding unnecessary surgery.